Inhibition of the Ras oncoprotein reduces proliferation of hepatocytes in vitro and in vivo in rats - da Silva Morais, Alain; Saliez, Alain; Leclercq, Isabelle; Horsmans, Yves; Stärkel, Peter (Clinical science (1979), 2008)
Ras oncoproteins are probably implicated in normal and malignant cell growth in various organs. Inhibition of Ras interferes with cell proliferation of non-hepatic cells in vitro and in vivo. A potential role for Ras in normal and malignant hepatocyte proliferation prompted us to evaluate the impact of Ras inhibition by FTS (S-farnesylthiosalicylic acid) on hepatocyte proliferation in vitro in the human hepatic tumour cell line HepG2 and in vivo after PH (partial hepatectomy) in rats. Rats were administered with FTS intraperitoneally (1, 8 and 16 h after PH) and killed 12, 24 and 48 h after PH. Cell proliferation, phosphorlyation of members of the MAPK (mitogen-activated protein kinase) pathway and levels and activity of cell cycle effectors (cyclin D, cyclin E, Cdk2 and Cdk4) were assessed in FTS-treated rats compared with controls. FTS significantly decreased overall cell count, PCNA (proliferating-cell nuclear antigen) expression and BrdU (bromodeoxyuridine) incorporation into HepG2 cells after 7 days of culture. FTS treatment significantly reduced BrdU incorporation and PCNA expression in hepatocytes after PH. Unlike control rats, cell-membrane expression of Ras was decreased in FTS-treated animals after PH, resulting in decreased Raf membrane recruitment and phosphorylation and in reduced phosphorylation of ERK1/2 (extracellular-signal-regulated kinase 1/2). The antiproliferative effect of FTS was linked to a decrease in expression and activity of the cyclin E/Cdk2 complex, without affecting cyclin D and Cdk4. Ras inhibition by FTS significantly decreased proliferation of HepG2 cells and normal hepatocytes after a strong and highly synchronized proliferation stimulus elicited by PH. The inhibitory effect was at least partially mediated by inhibition of Ras/Raf/MAPK signalling. It appears worthwhile to evaluate the impact of Ras inhibition on the development of hepatocarcinomas in vivo in adequate animal models.